1998
DOI: 10.1111/j.1699-0463.1998.tb01367.x
|View full text |Cite
|
Sign up to set email alerts
|

Epstein‐Barr virus strain characterization

Abstract: Munch M. Epstein-Barr virus strain characterization. APMIS 106: 425433, 1998.The Epstein-Barr virus (EBV), a ubiquitous human herpesvirus originally described in cultured lymphoblasts from African Burkitt's lymphoma, is the causative agent of infectious mononucleosis, but appears to be involved in the pathogenesis of a variety of diseases. EBV has the ability to establish lifelong persistent infection, where only a restricted pattern of the viral proteins is expressed. Periodic reactivation of EBV occurs, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…43 However, to date there are no in vivo data indicating that 30 bp deletion mutants show altered function when compared with EBV strains without the 30 bp deletion. [44][45][46][47] In mainland Japan, Mori et al also reported the 30 bp deletion of the LMP-1 gene in 91.7% of EBV related gastric carcinoma and 83.3% of throat washings from healthy adults. 48 In our present study, the LMP-1 genes of the type A virus from the mainland all showed the 30 bp deletion and in Okinawa the 30 bp deletion was seen in 97.0% of the EBV type A infected patients.…”
Section: Discussionmentioning
confidence: 99%
“…43 However, to date there are no in vivo data indicating that 30 bp deletion mutants show altered function when compared with EBV strains without the 30 bp deletion. [44][45][46][47] In mainland Japan, Mori et al also reported the 30 bp deletion of the LMP-1 gene in 91.7% of EBV related gastric carcinoma and 83.3% of throat washings from healthy adults. 48 In our present study, the LMP-1 genes of the type A virus from the mainland all showed the 30 bp deletion and in Okinawa the 30 bp deletion was seen in 97.0% of the EBV type A infected patients.…”
Section: Discussionmentioning
confidence: 99%
“… (Berger et al, 1999; Chang et al, 2006; Chang et al, 1995; Chen et al, 1996b; Cheung et al, 1998; Cheung et al, 1996; Chiang et al, 1999; Correa et al, 2004; D’Addario and Chauvin, 2000; Dolcetti et al, 1997; Fassone et al, 2002; Guiretti et al, 2007; Gutierrez et al, 2000; Hayashi et al, 1997; Itakura et al, 1996; Jeon et al, 2004; Khanim et al, 1996; Lin et al, 2004; Lindsey et al, 2008; Nguyen-Van et al, 2008; Plaza et al, 2003; Sandvej et al, 1997; Santon and Bellas, 2001; Santon et al, 1995; See et al, 2008; Sung et al, 1998; Tan et al, 2003; Tang et al, 2008; Tao et al, 1998; Tiwawech et al, 2008; Trimeche et al, 2007; Vallat-Decouvelaere et al, 2002; Zhang et al, 2002; Zhou et al, 2001) (Barozzi et al, 1999; Berger et al, 1999; Chang et al, 1995; Cheung et al, 1996; Khanim et al, 1996; Lin et al, 2004; Lin et al, 1995; Lin et al, 2003; Santon and Bellas, 2001; See et al, 2008; Shu and Tu, 2000; Tan et al, 2003; Tang et al, 2008; Zhou et al, 2001) …”
Section: Figures and Tablesmentioning
confidence: 99%
“…Some lytic cells were in mitosis (data not shown), in accordance with previous observations suggesting that EBV activation may be intimately linked with specific stages of the cell cycle. 32,52 Before, during and after release of EBV from lytically infected cells, it was impossible to discriminate between individual viral particles, but we estimated the number of viral copies to exceed several hundred per cell.…”
Section: Determination Of Ebv Latent or Lytic Infection Ee Leenman Et Almentioning
confidence: 99%